The Role and Function of Surveyors in the Maintenance of Medical Equipment in Hospitals (Literature Review) - Ahyar Wahyudi; Hisnindarsyah; Friedrich Max Rumintjap; Nurhikmah; Buyung Nazeli; Magdalena Sumico; Listyo Yuwanto (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article attempts to delve deeper into the role and function of a surveyor in assessing a healthcare-related element. Through accreditation bodies, a surveyor is expected to be more proactive in carrying out their role and functions. This article employs a literature review by attempting to distill insights from various studies and expert opinions, as well as guidelines published by the Ministry of Health. Through this article, an illustration and a thought on how healthcare equipment in hospitals should be treated are conveyed. As a conclusion from this article, understanding healthcare equipment is crucial, and the role of a surveyor should be optimized. The surveyor's role as a companion and evaluator in this context becomes an essential element in ensuring innovation and the highest standards in healthcare equipment management in hospitals.